"Protect someone, become yourself": How the Japanese military reinvents childhood for the 21st century. (August 2020) - Frühstück, Sabine
Military establishments the world over invest in multi-faceted and paradoxical relationships to children and childhood. This article aims to examine how the Japanese military today engages children and childhood in order to mold their public image, legitimize their missions, appease parents, and recruit the young.